Respuesta del banano a la aplicación de bacteria fijadoras de nitrogeno en el sitio la union del cantón Machala - Carrión Ordoñez, Danny Paúl (2013)
In the Kimberley banana plantation planted with Cavendish clone, site Machala Canton Union, the assay was performed to introduce patented nitrogen-fixing bacteria as Twin N alone and in association with different levels of ammonium nitrate. The objectives were: 1. Evaluate the effect of the bacteria in the growth Twin N fruit, 2. Determine the yield and quality of banana and 3. Perform economic analysis. The treatments applied to the experimental units with 20 useful plants distributed in random blocks with three replications: Twin N 100% T1, T2 Twin + 25% ammonium nitrate, T3 Twin N +50% ammonium nitrate, T4 Twin N +75% ammonium nitrate, T6. 100% ammonium nitrate, T7. Witness all. The variables evaluated were: plant height to 30,60,90,120,150, 180 days Number of leaves at the 30,60,90,120,150,180 days pseudostem thickness, number of hands per bunch, bunch weight, cluster index case; mass root at the beginning and end of the trial. In the analysis of variance and Duncan tests with P <0.05, no significant differences were found for the averages of treatments and height growth rates were fitted to a linear model. In the bunch weight, number of hands and ratio not found the treatments showed increases in weight without exceeding the ranges of Duncan, the root weight in the analysis of variance gave significant and highly significant results for the analyzes before and after the test.